Record-low 2025 and 2026 ice extents restore Arctic winter sea-ice decline - Duo Chan; Alessandro Silvano; Simon A. Josey (Proceedings of the National Academy of Sciences, 2026)
Recent analyses have suggested that the decadal rate of Arctic winter sea-ice extent decline weakened in the early 2020s, with 20-y trends becoming statistically insignificant. Here we show from more up-to-date observations that the exceptionally low 2025 and 2026 ice extent winters reversed this picture, with sea-ice extent during the growth and peak phases returning to record lows and 20-y decline trends becoming significant again. Further analysis of CMIP6 model analogues shows that the observed 2025 decline was unusual but physically plausible under comparable Arctic warming, and is more consistent with ongoing winter sea ice reduction than with a return to values seen in the early 2020s.